On the (s,t)-Pell and (s,t)-Pell-Lucas Polynomials - Srisawat, Somnuk; Sriprad, Wanna (Progress in Applied Science and Technology, 2021)
In this paper, we introduced the generalization of Pell and Pell-Lucas polynomials, which are called -Pell and - Pell-Lucas polynomials. We also give the Binet formula and the generating function for these polynomials. Finally, we obtain some identities by using the Binet formulas.